2021
DOI: 10.1021/acs.jpcb.0c10740
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Rational Control of Peptide–Surface Complexes

Abstract: Understanding peptide−surface interactions is crucial for programming self-assembly of peptides at surfaces and in realizing their applications, such as biosensors and biomimetic materials. In this study, we developed insights into the dependence of a residue's interaction with a surface on its neighboring residue in a tripeptide using molecular dynamics simulations. This knowledge is integral for designing rational mutations to control peptide−surface complexes. Using graphene as our model surface, we estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…We note that each Ncp analogue contributes a difference of ∼10 kJ/mol ΔF ads , which constitutes about 1/6 of the difference in ΔF ads difference for a whole chain. Our observation is consistent with the work of Dasetty and Sarupria 58 which also found that the adsorption free energy of unstructured peptides on graphene is dominated by the strongly adsorbing amino acids. The preference of aromatic groups to close-packed metal surfaces via many-body dispersion has been documented in related ab initio studies 59,60 and is well captured by the GolP-CHARMM FF (cf.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…We note that each Ncp analogue contributes a difference of ∼10 kJ/mol ΔF ads , which constitutes about 1/6 of the difference in ΔF ads difference for a whole chain. Our observation is consistent with the work of Dasetty and Sarupria 58 which also found that the adsorption free energy of unstructured peptides on graphene is dominated by the strongly adsorbing amino acids. The preference of aromatic groups to close-packed metal surfaces via many-body dispersion has been documented in related ab initio studies 59,60 and is well captured by the GolP-CHARMM FF (cf.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…Other authors have carried out studies of peptide absorption over graphene in the context of single amino acid Δ A ads . They have found that (i) single amino acid affinities are not sufficient to predict adsorption of peptides as there are cooperative effects related to the amino acid molecular context and (ii) that the adsorption process involves conformational changes which expose stronger binders and that the surface selects certain conformations due to the latter. Quite interestingly, the ΔSASA ads is a descriptor that encompasses all these factors, as it depends on the protein configuration, which is in turn a function of the molecular context of each amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tripeptides allows an exploration of how the immediate environment around each central residue, as influenced by the residues flanking it on either side, can modify the residue/surface contact in aqueous conditions. Such tripeptide MD simulation studies have been reported for materials such as graphene [ 42,43 ] and gold [ 44 ] surfaces. However, the use of these tripeptide data has not been used to directly inform materials‐binding sequence design.…”
Section: Introductionmentioning
confidence: 91%